INTEGRASI ILMU DAN MORAL: TANTANGAN DAN PELUANG DALAM MEMBANGUN MASYARAKAT BERADAB - Lubis, Khoirunnisaiyah; Hasibuan, Dina Sari; Darpansyah, Darpansyah; Maksum, Hasan; Siregar, Faisal Efendi; Siregar, Ifdlol Amarullah (LPPM Universitas Labuhanbatu, 2025)
Penelitian ini membahas tema